Recoding the city thinking, planning, and building the city of the nineteenth century - Hentschel, Britta 1977-; Hentschel, Britta 1977-; Stühlinger, Harald R. 1970-; Stühlinger, Harald R. 1970-; Damjanović, Dragan 1978- (Jovis, 2019)
"In the nineteenth century, cities and urban societies were subject to enormous shifts of power. The founding of the nation-states in Europe, industrialization, and the increased mobility that went along with them were accompanied by tremendous social change. New parties strove to participate in shaping society, as well as urban space. New functions and activities not only promoted the physical expansion of the developing capitals and metropolities, but also required a new coding of exisiting urban structures to meet the changing requirements and expectations regarding urban life and society. Recoding the city asks about the intentions and interests of the protagonists who shaped the city of the nineteenth century. Under what conditions did they succeed in inserting themselves into, overwriting, or - if necessary - even rewriting the exisiting urban structures? Against a background of growing competition between cities, public space increasingly became a medium that conveyed meaning, but also a battleground for ideas and demands. Representing an overview of international research initiatives, the authors examine whether and in what way this recording of the city in the nineteenth century still has an influence on our everyday life today."
Keywords: Geschichte 1800-1900; Stadtplanung; Städtebau; Stadtentwicklung; Architektur; Stadtgeschichte; Stadtgesellschaft; Städte; öffentliche Raum; Aufsatzsammlung